2011
DOI: 10.1051/epjconf/20111305001
|View full text |Cite
|
Sign up to set email alerts
|

Nonextensive statistical mechanics: Applications to high energy physics

Abstract: Abstract. Nonextensive statistical mechanics was proposed in 1988 on the basis of the nonadditive entropyThis theory extends the applicability of standard statistical mechanics in order to also cover a wide class of anomalous systems which violate usual requirements such as ergodicity. Along the last two decades, a variety of applications have emerged in natural, artificial and social systems, including high energy phenomena. A brief review of the latter will be presented here, emphasizing some open issues.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 60 publications
0
6
0
Order By: Relevance
“…Results obtained for the Alps revealed that the frequency distribution of the modelled failure volumes obeys a power-law with a scaling exponent in the range of the known empirical values (Brunetti et al, 2009a), and exhibits a distinct "rollover" for small size failures. Chen et al (2011) proposed an alternative way for describing the scaling properties of landslide sizes exploiting non-extensive statistical mechanics, or Tsallis statistics (Tsallis, 1988(Tsallis, , 1999(Tsallis, , 2011, a formal extension of the Boltzmann-Gibbs statistics. This approach relies on the postulate that a system composed by two independent statistical systems has an entropy given by the entropies of the two subsystems plus a correction term dependent on a parameter that controls the degree of non-additivity.…”
Section: Comparison With Other Modeling Approachesmentioning
confidence: 99%
“…Results obtained for the Alps revealed that the frequency distribution of the modelled failure volumes obeys a power-law with a scaling exponent in the range of the known empirical values (Brunetti et al, 2009a), and exhibits a distinct "rollover" for small size failures. Chen et al (2011) proposed an alternative way for describing the scaling properties of landslide sizes exploiting non-extensive statistical mechanics, or Tsallis statistics (Tsallis, 1988(Tsallis, , 1999(Tsallis, , 2011, a formal extension of the Boltzmann-Gibbs statistics. This approach relies on the postulate that a system composed by two independent statistical systems has an entropy given by the entropies of the two subsystems plus a correction term dependent on a parameter that controls the degree of non-additivity.…”
Section: Comparison With Other Modeling Approachesmentioning
confidence: 99%
“…[74]. For more details about the non-extensive statistics application in various fields in physics , cosmology and astronomy see [54,[75][76][77][78][79].…”
Section: Essential Features Of Non-extensive Statisticsmentioning
confidence: 99%
“…Complex systems are not used only in the domain of physics but also in other domains like biology, economics, and so on [11]. For more details about the non-extensive statistics application in various fields in physics and astronomy see References [5,[12][13][14][15][16]. Specifically, many systems deviate from the BG statistics, and it was necessary to generalize the original ones.…”
Section: Introduction Historical Review and Introductory Remarksmentioning
confidence: 99%